The Use of Slang among Teenagers in Pidie - Junaidi Junaidi; Asriani Ariani; Nurul Azmi; Mujiburrahman Mujiburrahman; Vera Wardani; Nuraiza Nuraiza (International Conference on Multidisciplinary Research, 2022)
This research is field research aiming to describe the use of slang among teenagers in Pidie. The method used was descriptive-analytical. The data came from Acehnese-speaking teenagers from various social environments in Pidie, Aceh. Data collection was carried out using uninvolved conversation, interviews with inducement technique, recording and note-taking techniques. The data were then analyzed using qualitative analysis techniques that consisted of several stages, namely selecting, identifying, classifying, reducing, presenting data, and drawing conclusions. The results showed that teenagers in Pidie use several types of slang: (a) basic word slang, (b) affix, (c) reduplicated slang, (d) abbreviated slang, (e) slang of crosses, (f) reversal, (g) slang from foreign languages, (h) slang resembling a foreign language, (i) euphemism slang, (j) dysphemism slang, (k) code-mixing slang, (l) pun slang, and (m) crossbred slang. Keywords: slang language, slang use, forms of slang, teenagers.